2020
DOI: 10.3389/fimmu.2020.01972
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Has Long-Lasting Effects on Circulating Follicular Regulatory T Cells in Kidney Transplant Recipients

Abstract: Background: FoxP3 + follicular regulatory T cells (Tfr) have been identified as the cell population controlling T follicular helper (Tfh) cells and B cells which, are both involved in effector immune responses against transplanted tissue. Methods: To understand the biology of Tfr cells in kidney transplant patients treated with tacrolimus and mycophenolate mofetil (MMF) combination immunosuppression, we measured circulating (c)Tfh and cTfr cells in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…There has also been a trend in some studies (100) of a positive Tfr : Tfh associating with less DSA formation. However, Niu et al (61), found patients with anti-HLA antibodies or DSA at 5-7 years post-transplant or any form of rejection had similar bTfr and bTfh cell numbers as those without antibodies or rejection. This is in opposition to Macedo et al (104), who demonstrated lower Tfh.…”
Section: Longer-term Immunosuppressionmentioning
confidence: 96%
See 3 more Smart Citations
“…There has also been a trend in some studies (100) of a positive Tfr : Tfh associating with less DSA formation. However, Niu et al (61), found patients with anti-HLA antibodies or DSA at 5-7 years post-transplant or any form of rejection had similar bTfr and bTfh cell numbers as those without antibodies or rejection. This is in opposition to Macedo et al (104), who demonstrated lower Tfh.…”
Section: Longer-term Immunosuppressionmentioning
confidence: 96%
“…However, Niu et al. ( 61 ), found patients with anti-HLA antibodies or DSA at 5–7 years post-transplant or any form of rejection had similar bTfr and bTfh cell numbers as those without antibodies or rejection. This is in opposition to Macedo et al.…”
Section: Role Of Tfr In Human Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in renal transplant recipients have demonstrated increased Tfh cell numbers before the development of donor-specific antibodies (DSA), in association with antibody-mediated rejection (ABMR) or with the development of anti-HLA antibodies (36)(37)(38). Furthermore, anti-rejection therapy with alemtuzumab significantly lowers the number of Tfh cells in kidney transplant recipients and contributes to the stable status of the kidney transplant (39). A study compared the proportion and function of follicular helper T cells in the blood between patients with operative tolerance and patients with stable graft function.…”
Section: Differences In B Cells Between Pretreatment and Posttreatmentmentioning
confidence: 99%